Quality Management in Social Work in the Netherlands: Principles and Approach - Braakenburg, Henri (Socialinė teorija, empirija, politika ir praktika, 2001)
The development of social work quality management in the Netherlands is presented in the article. There are two parts of the article. The development of social work quality conception and policy is described in the first part of the article. Prior to 1970 the paternalistic approach was dominant in the field of social care quality – the legitimacy of organization was dependent on the standards and rules managed by the authorities. Later due to the increasing complexity and the specialization in the care sector , the idea of a self-governing system emerged and was supported by the actors of social care system. The providers, insurers and clients’ organizations were expected to ensure quality by mutual agreement. At present day the quality of social work is understood in the perspective of total quality management in Netherlands. Total quality management is the best strategy in order to make trade offs between different interests and understandings of social work quality. The methods and instruments to further the quality in to practice are presented in the second part of the article.